Reactor Core Conversion Studies of Ghana Research Reactor – 1 and Proposal for Addition of Safety Rod - Odoi, H.C. (University of Ghana, 2014)
The inclusion of an additional safety rod in conjunction with a core conversion study of Ghana Research Reactor-1 (GHARR-1) was carried out using neutronics, thermal hydraulics and burnup codes. The study is based on a recommendation by Integrated Safety Assessment for Research Reactors (INSARR) mission to incorporate a safety rod to the reactor safety system as well as the need to replace the reactor fuel with LEU. Conversion from one fuel type to another requires a complete re-evaluation of the safety analysis. Changes to the reactivity worth, shutdown margin, power density and material properties must be taken into account, and appropriate modifications made. Neutronics analysis including burnup was studied followed by thermal hydraulics analyses which comprise steady state and transients. Four computer codes were used for the analysis; MCNP, REBUS, PLTEMP and PARET. The neutronics analysis revealed that the LEU core must be operated at 34 kW in order to attain the flux of 1.0E12 n/cm2.s as the nominal flux of the HEU core. The auxiliary safety rod placed at a modified irradiation site gives a better worth than the cadmium capsules. For core excess reactivity of 4 mk, 348 fuel pins would be appropriate for the GHARR-1 LEU core. Results indicate that flux level of 1.0E12 n/cm2.s in the inner irradiation channels will not be compromised, if the power of the LEU core is increased to 34 kW. The GHARR-1 core using LEU-UO2-12.5% fuel can be operated for 23 shim cycles, with cycle length 2.5 years, for over 57 years at the 17 kW power level. All 23 LEU cycles meet the ~ 4.0 mk excess reactivity required at the beginning of cycle. For comparison, the MNSR HEU reference core can also be operated for 23 shim cycles, but with a cycle length of 2.0 years for just over 46 years at the 15.0 kW power level. It is observed that the GHARR-1 core with LEU UO2 fuel enriched to 12.5% and a power level of 34 kW can be operated ~25% longer than the current HEU core operated at 30 kW. Based on the results presented in this report, it is concluded that the conversion of the GHARR-1 to LEU core is not likely to compromise safety nor increase the frequency/severity of any of the postulated design basis accidents identified in the current approved SAR.
Thesis (PhD) - University of Ghana, 2014